If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9y = -82 Solving 2x + 9y = -82 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. 2x + 9y + -9y = -82 + -9y Combine like terms: 9y + -9y = 0 2x + 0 = -82 + -9y 2x = -82 + -9y Divide each side by '2'. x = -41 + -4.5y Simplifying x = -41 + -4.5y
| 10*x^1/3=9 | | 3x^2-3=-6 | | -50=5w | | 15.7/x=0.7 | | 2x-4=3y+8 | | 3x+2-y=0 | | 2x-4+3y+8=5y+x+8 | | 9.25=-logx | | 720=3x+8y | | In(1+6x)=1673 | | 8p-40= | | 2x+4+2=x+10 | | 152.50=3x+8 | | 3.5+0.2p=6.1 | | -4(x+2)=x+2 | | 2(2x+2)=5(x+1) | | 152.50=8x+3 | | (M+2)(m-5)=0 | | 7(x+1)=5x+9 | | -2(r+5)=0 | | (1ab*3xy)-n= | | 4+5=3x | | (3x+4)=(x-5) | | 10/15=x/80 | | f(7)=2x+1 | | 7(y+2)=21 | | f(7)=2+1 | | 2/3v=2-43 | | -24-3r=9 | | x*2+9x+7=0 | | 2(d-6)=3d-1 | | 3/2p-2=-1 |